Local community’s intention to participate in ecotourism development: a case of local community in Bakun, Sarawak / Farah Fadhilah Rosdi - Rosdi, Farah Fadhilah (2018)
The purpose ofthis research is to investigate the relationship between potential economic benefits, potential social benefits and potential environmental benefits towards local community’s intention to participate in ecotourism development. Also, this research aims to identify which ofthe independent variables provide more influence or impact towards the local community’s intention to participate in ecotourism development. A sample of 120 were collected and analyzed. The findings revealed that there is a significant relationship between potential economic benefits, potential social benefits, and potential environmental benefits with local community’s intention to participate in ecotourism respectively. It is also concluded that potential environmental benefits has the biggest influence on the local community's intention to participate in ecotourism development. In addition, recommendation are also suggested and discussed.